Predicting Pathological Fractures at Metastatic Humeral Lesions. Issue 2 (27th April 2023) - Tat, Jimmy; Bodansky, David; Sheth, Ujash; Ung, Yee; Whyne, Cari; Nam, Diane
Abstract : Background: The humerus is the second most common site of metastatic disease involving long bones, yet it is still unclear which patients are at high risk for a fracture and may require prophylactic surgical fixation. The goal of this study was to assess the validity of the Mirels score to predict fractures of metastatic lesions in the humerus. Methods: We performed a retrospective electronic chart review of patients with humeral metastases at our institution (2005 to 2021), with 188 patients meeting the inclusion criteria. Sixty-one of the patients developed a fracture during follow-up. The metastatic humeral lesions were scored according to the Mirels rating system and additional radiographic criteria (cortical breach, location within the humerus, number of lesions). The predictive value of each Mirels score cutoff for fracture was assessed using sensitivity, specificity, area under the receiver operating characteristic curve (AUC), and multivariate logistic regression. Survivorship until fracture was analyzed for each Mirels score cutoff using Kaplan-Meier curves and the log-rank test. Significance was set at p < 0.01. Results: There were no significant differences in age, sex, side of the lesion, type of malignancy, and radiation dose between the groups with and without fracture (all p > 0.01). A Mirels score of ≥8 points had the best predictive profile, with sensitivity of 83.6%, specificity of 79.5%, and AUC of 0.82 (95% confidence interval [CI], 0.75 to 0.88, p < 0.01). A logistic regression model also demonstrated that a Mirels score of ≥8 (odds ratio = 5.8, 95% CI = 1.9 to 18.2, p < 0.01) and a cortical breach (odds ratio = 21.0, 95% CI = 5.7 to 77.2, p < 0.01) were significant predictors of pathological fracture. No other radiographic characteristics were found to be significant predictors of fracture. Conclusions: This study indicated that a Mirels score of ≥8 points had the best predictive profile for anticipating fractures at a metastasis in the humerus. This is in contrast to the traditional Mirels definition of an impending pathological fracture that is used for the lower extremity, a score of ≥9. Additionally, the presence of a cortical breach was a significant predictor of fracture risk. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.